CARDIOVASCULAR ADAPTATION TO PHYSICAL ACTIVITY IN ETHNICALLY DIFFERENT YOUNG ATHLETES. (June 2018) - Galanti, G.; Tosi, B.; Orlandi, M.; Mascherini, G.; Giannelli, C.; Stefani, L.; Toncelli, L.; Boddi, M.; Modesti, P.A.
Abstract : Objective: Cardiovascular adaptation to intense physical training is determined by many factors including age, gender, body size, load training, ethnicity and blood pressure response to exercise. Our retrospective study aimed to assess secondary left ventricular (LV) remodelling to exercise, in terms of interventricular septum (IVS) and posterior wall (PW) thickness, in young male black soccer players (BP) compared to male white soccer players (WP). Design and method: 77 BP and 53 WP (17.8 years old), trained with the same load and having the same lifestyle, were evaluated with maximal ergometric test, echocardiography and speckle-tracking global longitudinal strain (GLS). 30 younger BP and 27 WP (13.2 years old) were selected and followed up for 4 years. Results: In the older group of athletes blood pressure response to exercise and GLS were comparable in BP and WP, whereas IVS and PW thickness were significantly higher in BP (IVS: 10.04 ± 0.14 and 9.35 ± 0.10 mm, p < 0.001; PW: 9.70 ± 0.20 and 9.19 ± 0.10 mm, p < 0.05; in BP and WP respectively). Considering the younger group of athletes no significant difference was found in blood pressure while a higher LV remodelling was detected (IVS = 9.29 ± 0.3 and 8.53 ± 0.12 mm, p < 0.002; PW = 9.01 ± 0.2 and 8.40 ± 0.20, p = 0.1; in BP and WP respectively). The degree of LV remodelling was proportional with body-size and LV mass during the four years of follow-up (IVS = 10.52 ± 0.17 and 9.03 ± 0.22 mm, p < 0.001; PW: 10.06 ± 0.17 and 8.26 ± 0.19 mm, p < 0.001; in BP and WP respectively). Conclusions: Since no significant difference in blood pressure response to exercise was detected and since all principal determinants of cardiovascular response to exercise were overcome by specific selection of all athletes enrolled, ethnicity seems to remain the principal factor involved in cardiovascular adaptation to physical training.